4. nacionalna konferenca o varnosti v lokalnih skupnostih: sklepne ugotovitve raziskovanja (2015–2018): konferenčni zbornik (University of Maribor Press, 2018)
4th National Conference on Local Safety and Security: Research Findings (2015–2018): Conference proceedings. The conference proceedings present peer reviewed papers presented from the fourth national conference on Local safety and security in Slovenska Bistrica in December 2018. A lead topic of the conference summarizes research findings on local safety and security which were done in the framework of the research programme carried out at the Faculty of Criminal Justice and Security, University of Maribor. Papers in the proceedings discuss various aspects of local safety and security, including perception of safety and security and crime prevention (perception of sources of threats, perception of police work, perception of safety in urban areas, the impact of the welfare state on safety and security and situational crime prevention); and various perspectives on local safety and security (safety in town municipalities, position of migrants in local communities, perception of armed forces, information security of residents and security of economic entities).